BNT162b2 coronavirus disease-2019 vaccination accelerated rheumatoid arthritis disease activity in chronic eosinophilic pneumonia: A case report. Issue 39 (30th September 2022) - Morikawa, Moeko Murano; Harada, Masanori; Kishimoto, Ei; Suzuki, Kosuke; Nakagawa, Emiko; Hiramatsu, Toshiya; Nakai, Shogo; Murakami, Yurina; Nishimoto, Koji; Matsushima, Sayomi; Uto, Tomohiro; Imokawa, Shiro
Abstract : Rationale: The relationship between rheumatoid arthritis (RA) and eosinophilic inflammation is unclear. According to recent studies, it has been suggested that T helper 2 cell responses play a role in the inhibition of RA. It is unclear how the immunological response after coronavirus disease-2019 (COVID-19) vaccination affects T cell immune reactions. Patient concerns and diagnoses: Here, we report the case of an 88-year-old woman diagnosed with RA and chronic eosinophilic pneumonia (CEP). She was diagnosed with CEP about 20 years ago, and, through steroid treatment, she improved and had no relapse for 16 years. At the time of diagnosis of CEP, the rheumatoid factor (RF) was increased; however, there were no joint symptoms. After receiving the COVID-19 vaccine, joint and respiratory symptoms gradually worsened. Laboratory examinations showed increased RF, anti-cyclin citrullinated peptide antibody, and peripheral absolute eosinophil count. Musculoskeletal ultrasonography showed synovitis. Intervention and outcome: Methylprednisolone pulse therapy improved respiratory and joint symptoms immediately; RA and CEP stabilized with no relapses. Lessons: Eosinophilic and rheumatoid reactions following COVID-19 vaccination were an-reported adverse events. Eosinophilic inflammation might be reflected on an anti-inflammatory reaction in initial phase of RA.